Urgensi Pelaksanaan Program Kebijakan Industri Hijau sebagai Upaya Melestarikan Lingkungan Hidup di Indonesia (RechtJiva, 2025)
National industries must anticipate the rise of environmental issues in national and international trade, in order to remain competitive with other countries. The Ministry of Industry has responded to this by including Green Industry as an important part of the National Industrial Development Master Plan 2015 – 2035. To encourage the industrial sector to apply the principles of green industry. Therefore, this study is aimed at measuring environmental performance for several industries in Indonesia so that they can be aware of their readiness to apply green industry standards.  This researchuses normative methods, normative legal research is defined as research that refers to legal norms contained in laws and regulations and court decisions. Normative legal research can also be referred to as doctrinal legal research.  The application of environmental management and the concept of green industry requires a comprehensive understanding. For this reason, an integrated basic concept is needed. The concept of green industry is the integration of planning and implementation of environmental management in industrial management. It is called green industry  , which means an environmentally friendly industry. Environmental Management has been given a place in conjunction with the design process to the operation of an industry.